SISTEM KONTROL LEVEL TRANSMITTER PADA TANGKI FA-920 DI PT. SINTAS KURAMA PERDANA - Pratama, Andika; Rahmadewi, Reni (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2024)
Instrumentation is a very important tool in a measurement system, one of which is measuring the height of the liquid surface, this tool must be able to function properly in accordance with the instrumentation needs in the factory. Instrumentation is one of the factors that determine production results, where instrumentation tools measure, control, detect, analyze, both manually and automatically. Electric Differential Pressure Transmitter is a sensor that is used to measure the level of the liquid level as a tool to be read to the controller to the final setting.